2019
DOI: 10.2174/1573406414666180827112724
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Thiazolyl Substituted Bis-pyrazole Oxime Derivatives with Potent Antitumor Activities by Selectively Inducing Apoptosis and ROS in Cancer Cells

Abstract: Our synthetic bis-pyrazole oxime derivatives possess potent antitumor activities by selectively inducing apoptosis and ROS accumulation in cancer cells, which may hold great promise as therapeutic agents for the treatment of human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our study disclosed the selective growth inhibition of breast cancer cells, MDA-MB-468 corresponded to the 3f compound is associated with apoptosis pathway through ROS generation. Our results are in agreement with the literature (Xiong et al, 2019) that reported a novel thiazolyl substituted bis-pyrazole oxime compound selectively inhibited proliferation of colorectal cancer HCT116 cells by inducing apoptosis pathway through the promotion of intracellular ROS level. The therapeutic impact of a Pyrazole compound on angiogenesis in human umbilical vein endothelial cells (HUVECs) was studied by Zhang et al, (2011).…”
Section: Discussionsupporting
confidence: 93%
“…Our study disclosed the selective growth inhibition of breast cancer cells, MDA-MB-468 corresponded to the 3f compound is associated with apoptosis pathway through ROS generation. Our results are in agreement with the literature (Xiong et al, 2019) that reported a novel thiazolyl substituted bis-pyrazole oxime compound selectively inhibited proliferation of colorectal cancer HCT116 cells by inducing apoptosis pathway through the promotion of intracellular ROS level. The therapeutic impact of a Pyrazole compound on angiogenesis in human umbilical vein endothelial cells (HUVECs) was studied by Zhang et al, (2011).…”
Section: Discussionsupporting
confidence: 93%
“…In this work, the formation of the desired 1-(oxiran-2-ylmethyl)-3-aryl-1H-pyrazole-5-carboxylates by alkylation of easily accessible NH-pyrazoles [48] with 2-(chloromethyl)oxirane was optimized using 1a as a model compound. As shown in Table 1, reaction outcome is highly dependent on the choice of the base and the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic Procedures 3.2.1. General Procedure for Synthesis of Starting 3(5)-Aryl-1H-pyrazole-5(3)-carboxylates (1a-h) [48,65] To a 0.5 M solution of sodium ethoxide (1.1 eq) in ethanol, appropriate acetophenone (1 eq) and diethyl oxalate (1 eq) were added, and the resulting mixture was stirred at room temperature for 16 h in an inert atmosphere. Upon completion, the reaction mixture was quenched with 1 M HCl solution until neutral pH and extracted with ethyl acetate.…”
Section: Generalmentioning
confidence: 99%
“…Synthesis of ethyl 3(5)-aryl-4-bromo-1H-pyrazole-5(3)carboxylates 3a-c (ref. 43). An appropriate pyrazole 2a-c (1 eq.)…”
Section: Chemistrymentioning
confidence: 99%